2022
DOI: 10.1177/15589447221109632
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Distal Radius Fractures Under Wide-Awake Local Anesthesia: A Systematic Review

Abstract: Background: The purpose of this systematic review was to analyze the available literature on fixation of distal radius fractures (DRFs) under wide-awake local anesthesia no-tourniquet (WALANT), and to examine postoperative pain scores and functional outcomes, operative data including operative time and blood loss, and the frequency of adverse events. Methods: Embase, MEDLINE, Web of Science, and SCOPUS were searched from inception until May 2022 for relevant studies. Studies were screened in duplicate, and dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Every year, new reports that push boundaries are published. There are recent reports of wrist surgery, radius, and ulna fracture plating, elbow surgery, clavicle plating, and major limb amputations (71,72,73,74,75,76,77,78,79,80). Although the cost benefits of this approach in these cases are evident, the absolute indications for these procedures are not yet completely clear and are still limited to preferences or circumstances outruling other options (66,81,82,83).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Every year, new reports that push boundaries are published. There are recent reports of wrist surgery, radius, and ulna fracture plating, elbow surgery, clavicle plating, and major limb amputations (71,72,73,74,75,76,77,78,79,80). Although the cost benefits of this approach in these cases are evident, the absolute indications for these procedures are not yet completely clear and are still limited to preferences or circumstances outruling other options (66,81,82,83).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Because the main operating room and anesthesia support are no longer necessary, access to hand surgery has improved as WALANT technique usage has become more widespread, particularly in developing countries 43,44 . For instance, in a systematic review of patients with closed distal radius fractures, Gouveia et al concluded that the wide-awake local anesthesia method is a safe and effective option permitting patients to have surgery sooner, rather than waiting for availability of anesthesia services 45 . Thus, the WALANT alternative is important in locations where general anesthesia resources are limited 46 .…”
Section: Advantages Of the Walant Techniquementioning
confidence: 99%
“…It is estimated that avoiding their use in knee arthroplasty could prevent nearly 2000 serious adverse events per year in the UK alone ( 29 ). Similarly, wide-awake local anaesthesia no tourniquet (WALANT) surgery for adult upper limb orthopaedic operations has been increasing in popularity and has shown good clinical results with reduced risk and cost ( 30 , 31 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%